Recent Progress of Oral Functional Nanomaterials for Intestinal Microbiota Regulation - Wanneng Li; Minle Zhan; Yue Wen; Yu Chen; Zhongchao Zhang; Shuhui Wang; Dean Tian; Sidan Tian (MDPI AG, 2024)
The gut microbiota is closely associated with human health, and alterations in gut microbiota can influence various physiological and pathological activities in the human body. Therefore, microbiota regulation has become an important strategy in current disease treatment, albeit facing numerous challenges. Nanomaterials, owing to their excellent protective properties, drug release capabilities, targeting abilities, and good biocompatibility, have been widely developed and utilized in pharmaceuticals and dietary fields. In recent years, significant progress has been made in research on utilizing nanomaterials to assist in regulating gut microbiota for disease intervention. This review explores the latest advancements in the application of nanomaterials for microbiota regulation and offers insights into the future development of nanomaterials in modulating gut microbiota.